A differential‐free output feedback control for stabilization of continuous‐time LTI systems with Euler's approximation method. Issue 6 (16th August 2019) - Ghaffari, Valiollah
Abstract : A differential‐free output feedback control law is addressed to stabilize the continuous‐time linear time‐invariant control systems. For achieving the goal, a state‐feedback control scheme is firstly designed to meet the predefined control objectives and requirements. Then, an output feedback controller would be derived through the Euler's backward approximation. Therefore, the closed‐loop system is deliberately converted into a time‐delayed control system. The proposed control scheme will be designed by guaranteeing the stability of such time‐delayed system. Thus, a sufficient stability condition would be addressed in terms of the linear matrix inequity ( LMI ). Hence, feasibility of the mentioned LMI leads to stability of closed‐loop system with the differential‐free output feedback. The suggested continuous‐time controller is used in a typical dynamical system to design of a differential‐free control law. The applicability and also the effectiveness of the proposed control scheme would be shown by a numerical simulation.